TRAGEDY IN WORLD LITERATURE - F. K. Sherzhanova (PT. Antis International Publisher, 2024)
Objective: This study explores the genre of tragedy, tracing its origins and development within the literary traditions of world and Turkic peoples, with a particular focus on Karakalpak literature. It aims to analyze the scholarly perspectives on tragedy and drama and their evolution over time. Method: The research employs a comparative literary analysis, reviewing foundational works and contemporary studies on tragedy. It synthesizes insights from historical, cultural, and literary perspectives to provide a comprehensive understanding of the genre’s development in both global and regional contexts. Results: The findings reveal the nuanced emergence and adaptation of the tragedy genre within Turkic literature, highlighting its interplay with global literary traditions. The study underscores the critical contributions of Karakalpak scholars to understanding the genre, especially during its formative years and subsequent evolution. Novelty: This work offers a fresh synthesis of global and Turkic literary studies on tragedy, emphasizing its significance in Karakalpak literature. It bridges gaps in existing scholarship by contextualizing the genre within a broader cultural and literary framework.